CAR-NK cell therapy combined with checkpoint inhibition induces an NKT cell response in glioblastoma - Strassheimer, F.; Elleringmann, P.; Ludmirski, G.; Roller, B.; Macas, J.; Alekseeva, T.; Cakmak, P.; Aliraj, B.; Krenzlin, H.; Demes, M. C.; Mildenberger, Iris; Tonn, T.; et al. (British journal of cancer, 2025)
Glioblastoma is the most aggressive primary brain tumor with limited efficacy of established therapies, and a pronounced immunosuppressive tumor microenvironment. Targeting HER2 with local immunotherapy allows for high tumor specificity in the brain with physiologically very low expression. Monotherapy with CAR-NK cells targeted against HER2 has previously shown efficacy in medium-sized GL261/HER2 tumors.
Online veröffentlicht: 18. März 2025
Gesehen am 05.08.2025